1865 A Work-Training-Unit on the Neonatal Intensive Care Unit (NICU). An Optimal Learnig Climate?. (October 2012) - Wielenga, J; Hemmink, M; Willemsen, M; Bouwens, C; Boltje, J
Abstract : Background and Aims: On the NICU of the Women's and Children Clinic/Academic Medical Center in Amsterdam the Netherlands, newborns are transferred to regional hospitals for high dependency care. This had consequences for inexperienced nurses' preparation of their post graduate Intensive Care Neonatology training. These trainees had to work on the Intensive Care without the proper patients present. Therefore independency in caring was limited. To create a powerful and safe learning climate and to offer trainees the opportunity to become competent, a work-training-unit was established. Methods: Preconditions were decided on: presence of an adequate amount of coaches, training focussing on situational coaching, four newborns, one coach and two pre-course trainees in the day or evening shift and preferably no trainees in the night shift and daily reflection and evaluation. Coaches were trained how to supervise and enhance the competency, expertise and independency of the trainees. Results: On the work-training-unit the trainees were offered the opportunity to care for post-IC and high dependency newborns, under constant supervision of their coach. Trainees in the work-training-unit, achieved the acceptable level of functioning and usability sooner. An increase in performing nursing procedures and standard care in a uniform way was noticed. Trainees as well as coaches were extremely satisfied. Conclusions: The work-training-unit is a valuable addition to the learning possibilities of nurses as well as the organisation. It has positive side effects on work pressure, production and capacity but most of all it appears to be an optimal learning climate.